Leucine and tissue distribution of bulky and small neutral amino acids in rats: dissociation between transport and insulin-mediated effects - de Céspedes Montealegre, Carlos (1992)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 1992